DEVELOPMENT OF AN INSTRUMENT FOR TEACHERS TO CRAWL AUTISTIC SPECTRUM DISORDER IN ADOLESCENT SCHOOLCHILDREN (Interdisciplinary Studies Journal, 2025)
This study aims to present the development process and content evaluation of the screening tool for autism in adolescents. This instrument aims to quickly check for signs of autism in four domains: executive functions, communication, social skills and activities of daily living. The process involved: 1) reading the DSM-V; 2) development of questions; 3) analysis by expert judges/evaluators and; 4) pilot study with results from the ROC curve to evaluate the cutoff point of an instrument for detecting autism in children. The results indicate that when using the cutoff point, the instrument showed a good ability to correctly identify positive cases (75% sensitivity) and also a high rate of correct identification of negative cases (89% specificity). They also suggest that the instrument met all the requirements for structuring, relevance, credibility and balance, through understandable items, consistent with the characteristics related to what was proposed in the study.
Keywords: Autism; Psychometrics; Content Validation